Fairy moths of the genus Nemophora Hoffmannsegg, 1798 (Lepidoptera: Adelidae) from Myanmar, Thailand, Laos, Cambodia and Vietnam - Kozlov, Mikhail V. (Zootaxa, 2024)
This study provides a comprehensive account of 40 species (52 valid names and one preoccupied name) of the genus Nemophora Hoffmannsegg, 1798 described or recorded from Myanmar, Thailand, Laos, Cambodia and Vietnam. A key to the species based on external characters and on male genitalia is provided; 14 new species are described: N. auricapitella Kozlov, sp. nov., N. chalcoptera Kozlov, sp. nov., N. karsholti Kozlov, sp. nov., N. kuznetzovi Kozlov, sp. nov., N. meyi Kozlov, sp. nov., N. nielseni Kozlov, sp. nov., N. nieukerkeni Kozlov, sp. nov., N. nigripunctella Kozlov, sp. nov., N. punctifasciella Kozlov, sp. nov., N. rubicunda Kozlov, sp. nov., N. szabokyi Kozlov, sp. nov., N. thailandensis Kozlov, sp. nov., N. vietnamensis Kozlov, sp. nov. and N. yeni Kozlov, sp. nov. Lectotypes are designated for four species, including one junior synonym: Nemotois diplophragma Meyrick, 1938, Nemotois sinicella Walker, 1863, Nemotois cleodoxa Meyrick, 1922 and Adela satrapodes Meyrick, 1894. Eight new synonyms for four species are proposed: Nemophora badagongshana Liao, Hirowatari & Huang in Liao, Hirowatari, Yagi, Wang, Wang & Huang, 2023, syn. nov. of Nemophora aurifera (Butler, 1881); Nemotois chrysocharis Caradja, 1938, syn. nov. of Nemophora sinicella (Walker, 1863); Nemotois diplophragma Meyrick, 1938, syn. nov. of Nemophora melichlorias (Meyrick, 1907); Nemophora basalistriata Liao, Hirowatari & Huang in Liao, Hirowatari, Yagi, Wang, Wang & Huang, 2023, syn. nov. of Nemophora melichlorias (Meyrick, 1907); Nemotois limenites Meyrick, 1914, syn. nov. of Nemophora aurifera (Butler, 1881); Nemophora quadrata Liao, Hirowatari & Huang in Liao, Hirowatari, Yagi, Wang, Wang & Huang, 2023, syn. nov. of Nemophora aurifera (Butler, 1881); Nemotois rubrofascia formosicola Matsumura, 1931, syn. nov. of Nemophora sakaii (Matsumura, 1931); Nemotois servata Meyrick in Caradja, 1925, syn. nov. of Nemophora aurifera (Butler, 1881). Four new combinations are introduced: Nemophora aglaospila (Meyrick, 1928), comb. nov.; Nemophora cleodoxa (Meyrick, 1922), comb. nov.; Nemophora melichlorias (Meyrick, 1907), comb. nov.; and Nemophora sinicella (Walker, 1863), comb. nov. Of 40 species considered, 16 were recorded in Myanmar, 21 in Thailand, 4 in Laos, 4 in Cambodia and 13 in Vietnam.